2016
DOI: 10.5194/acp-16-11899-2016
|View full text |Cite
|
Sign up to set email alerts
|

Molecular composition of organic aerosols in central Amazonia: an ultra-high-resolution mass spectrometry study

Abstract: Abstract. The Amazon Basin plays key role in atmospheric chemistry, biodiversity and climate change. In this study we applied nanoelectrospray (nanoESI) ultra-high-resolution mass spectrometry (UHRMS) for the analysis of the organic fraction of PM2.5 aerosol samples collected during dry and wet seasons at a site in central Amazonia receiving background air masses, biomass burning and urban pollution. Comprehensive mass spectral data evaluation methods (e.g. Kendrick mass defect, Van Krevelen diagrams, carbon o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(94 citation statements)
references
References 87 publications
6
87
1
Order By: Relevance
“…The T3 site of GoAmazon2014/5 was chosen because it was expected (and was shown in Kourtchev et al, 2016) to be impacted by multiple distinct types of emissions. These include regional biogenic emissions (isoprene, MT, SQT, etc.…”
Section: Estimating Source Contributions To Potential Soa Using Multimentioning
confidence: 99%
See 1 more Smart Citation
“…The T3 site of GoAmazon2014/5 was chosen because it was expected (and was shown in Kourtchev et al, 2016) to be impacted by multiple distinct types of emissions. These include regional biogenic emissions (isoprene, MT, SQT, etc.…”
Section: Estimating Source Contributions To Potential Soa Using Multimentioning
confidence: 99%
“…Oxidation of ambient forest air dominated by biogenic emissions and urban air dominated by urban emissions has shown that ambient S/IVOCs are likely impor-tant precursors for ambient SOA formation from OH oxidation, but not for O 3 or NO 3 oxidation . In contrast to those locations, the atmosphere in the Central Amazon forest (downwind of Manaus) is influenced by mixed biogenic, urban, and biomass burning sources of SOA precursor gases Kourtchev et al, 2016), providing a unique opportunity to study the influence of anthropogenic activities on the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the region is a valuable laboratory, for example for studying the impact of anthropogenic emissions of air pollutants on atmospheric chemical composition. Although there are a number of studies involving the measurements of atmospheric pollutants in the Amazon region (e.g., Kuhn et al, 2010;Trebs et al, 2012;Baars et al, 2012;Artaxo et al, 2013), most of the contribution was published very recently with the results of the GoAmazon2014/5 project Alves et al, 2016;Pöhlker et al, 2016;de Sá et al, 2017;Kourtchev et al, 2016;Hu et al, 2016;Bateman et al, 2017;Cecchini et al, 2016;Jardine et al, 2016). In terms of numerical studies, only a few studies focusing the role of the anthropogenic emission sources in urban areas are available Andreae et al, 2012;Beck et al, 2013;Bela et al, 2015).…”
Section: S a Abou Rafee Et Al: Contributions Of Mobile Stationarymentioning
confidence: 99%
“…These unique compounds all contained high DBE values (9 or greater for C 16 -C 25 molecules), suggesting the presence of multiple double bonds or ring structures. In the Amazon, Kourtchev et al (2016) previously found a similar subset of these unidentified CHOS compounds in SOA samples, suggesting a biogenic influence. Many organosulfates and nitrooxy-organosulfates, previously reported in laboratory studies, ambient aerosols, and cloud water as derived from monoterpene oxidation (Boone et al, 2015;Hamilton et al, 2013;Iinuma et al, 2007aIinuma et al, , b, 2009Kristensen et al, 2016;Kristensen and Glasius, 2011;Lin et al, 2012;Mazzoleni et al, 2012;Nguyen et al, 2012b;Nozière et al, 2010;O'Brien et al, 2014;Pratt et al, 2013;Stone et al, 2012;Surratt et al, 2008), were detected in the biogenic-influenced cloud water samples (Table 2), also consistent with monoterpene emissions along the air mass trajectories (Guenther et al, 2006).…”
Section: Biogenic Influencementioning
confidence: 99%